2011
DOI: 10.1186/1746-1596-6-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Virtual telepathology in Egypt, applications of WSI in Cairo University

Abstract: Telepathology, the practice of pathology at a long distance, has advanced continuously since 1986. Today, fourth-generation telepathology systems, so-called virtual slide telepathology systems, are being used for education applications. Both conventional and innovative surgical pathology diagnostic services are being designed and implemented as well. We have a successful experience in Egypt in applying the static & dynamic techniques in a pilot project between the Italian Hospital in Cairo (NPO) and the Civico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
1
Order By: Relevance
“…The results of a similar binational consultation project between Egypt and Italy were reported in 2011. 90 Although the project ran for 7 years, no empirical data were reported. The authors reported that consultations were completed ''.on many problematic pathological cases.…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 99%
“…The results of a similar binational consultation project between Egypt and Italy were reported in 2011. 90 Although the project ran for 7 years, no empirical data were reported. The authors reported that consultations were completed ''.on many problematic pathological cases.…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 99%
“…21 Some pathology informatics rotations are now in place in several countries, including the United States and Canada. [22][23][24] An important challenge highlighted in the survey was balancing the need to develop skills for real practice as independent pathologists (mainly assessing glass slides) and the need to deve lop skills to pass the certification examination (through digital pathology training). Although digital whole-slide images are currently emerging as a tool for consultation and education, most reports suggest that these images are not yet ready for routine use in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Essam A make use of whole slide imaging technique of telepathology system to provide consultation on complicated pathological cases saving time, money, improving health care services and also sharing knowledge between Italy, UK and US [11].…”
Section: Literature Reviewmentioning
confidence: 99%